Androgens correlate with increased erythropoiesis in women with congenital adrenal hyperplasia. (25th July 2016) - Karunasena, Nayananjani; Han, Thang S.; Mallappa, Ashwini; Elman, Meredith; Merke, Deborah P.; Ross, Richard J.M.; Daniel, Eleni
Summary: Objective: Hyperandrogenism in congenital adrenal hyperplasia (CAH) provides an in vivo model for exploring the effect of androgens on erythropoiesis in women. We investigated the association of androgens with haemoglobin (Hb) and haematocrit (Hct) in women with CAH. Design: Cross‐validation study. Patients: Women with CAH from Sheffield Teaching Hospitals, UK (cohort 1, the training set: n = 23) and National Institutes of Health, USA (cohort 2, the validation set: n = 53). Measurements: Androgens, full blood count and basic biochemistry, all measured on the same day. Demographic and anthropometric data. Results: Significant age‐adjusted correlations ( P < 0·001) were observed for Ln testosterone with Hb and Hct in cohorts 1 and 2 (Hb r = 0·712 & 0·524 and Hct r = 0·705 & 0·466), which remained significant after adjustments for CAH status, glucocorticoid treatment dose and serum creatinine. In the combined cohorts, Hb correlated with androstenedione ( P = 0·002) and 17‐hydroxyprogesterone ( P = 0·008). Hb and Hct were significantly higher in cohort 1 than those in cohort 2, while there were no group differences in androgen levels, glucocorticoid treatment dose or body mass index. In both cohorts, women with Hb and Hct in the highest tertile had significantly higher testosterone levels than women with Hb and Hct in the lowest tertile. Conclusions: In women with CAH, erythropoiesis may be driven by androgens and could be considered a biomarker for disease control.